Profile and Bioactivity of Bioactive Compounds of Beauveria bassiana Fungi Entomopathogens of Endophytes as Plant Growth Boosters - Yusniwati Yusniwati; Trizelia Trizelia; Nurbailis Nurbailis; Magdalena Saragih Saragih (AGRIUM: Jurnal Ilmu Pertanian, 2023)
The purpose of this study was to identify bioactive compounds of Beauveria bassiana  entomopathogenic fungi derived from insect isolates of Leptocorisa oratorius and endophytic fungi B. bassiana from cocoa plants that have bioactivity as growth boosters.  The research was conducted in the laboratory of Biological Control, Faculty of Agriculture, Andalas University. The study was conducted for 4 months, using the GCMS method. From the results of the study, bioactive compounds identified as growth boosters of B. bassiana endofyt fungi from cocoa plants are compounds Acetic acid, Ethanoic acid, Ethylic acid, Glacial acetic acid, CH3COOH;  n- Hexadecanoic acid Hexadecanoic acid, Palmitic acid;  9-Octadecenoic acid (2)-(CAS), Oleic acid, Red oil, Oelsaure; octadecanoic acid (CAS) Stearic acid, n-Octadecanoicacid, vanilla; Ergosta-5,7,22-trien-3-ol, (3.,beta.,22 E) – (CAS), Ergosterol (CAS);  while  from the  entomopathogenic B. bassiana fungus from L. oratorius insects  are Acetic acid (CAS), Ethylic acid, vinegar acid, Ethanoic acid, CH3COOH, Dianhydromannitol; Isosorbide, D-Glucitol,1,4-3,6-dianhydro-(+)-D-Isosorbide Devicoran;  Hexadecanoic acid, methyl ester (CAS), Methyl palmitate, Uniphat A60;  n-Hexadecanoic acid Hexadecanoic acid, n- Hexadecanoic acid, Palmitic acid; 9-octadecenoic acid, methyl ester, (E)-elaidic acid; 9-octadecanoic acid (Z)-(CAS) , oleic acid, Red oil, Oelsauere; octadecanoic acid, stearic acid, -n-octadecanoic acid, Humko Industrene R; Ergosta-5,7,22-trien-3-ol, (3.beta.,22E)-CAS, Ergosterol (CAS)